(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
At a time when society is plunged into a deep moral crisis and speed is progressively becoming the mainstay of the entire principology of civil procedure, there is growing concern about the institute of bad faith litigation. The principle of procedural celerity is a legal norm whose desired content is the swift delivery of justice, a norm which is inspired by the belief that “justice delayed is injustice qualified”. In fact, it is an ideal that can be achieved through countless measures: making oral communication prevail in the parties’ arguments and in the presentation of evidence over a judgment based on written records; restricting the investigation of the case to as few hearings as possible (or, if possible, to a single concentrated hearing); preventing continuous interruptions in the procedural process caused by appeals filed by the parties against decisions made by the judge on incidents arising in the course of the case; making it exceptional to grant suspensive effect to appeals; shortening procedural deadlines; eliminating unnecessary formalities, prioritizing the instrumentality of forms; anticipating the reversible practical effects of the final relief sought. However, one of the most important ways of achieving procedural speed is undoubtedly the tough fight against acts of delay, bad faith litigation and abusive exercise of the right of defense. Civil proceedings cannot be swift unless they are characterized by moral clarity. In addition to all sorts of problems and limitations that the Judiciary suffers from in order to deliver justice quickly (lack of judges and civil servants, lack of human training, low level of computerization of procedures, precarious facilities, lack of working materials, budget restrictions, etc.), there is one factor that slows down the process and which the Judiciary is very much responsible for eradicating: bad faith.